Long-Term Permissible Load Currents of Single-Core Cables with a Voltage of 10 kV with Cross-Linked Polyethylene Insulation of Various Designs - M. E. Vysotski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
There is a large number of factors that affect the long-term permissible load currents of power cables, including environmental conditions, the method of laying, as well as the geometric, thermal and electrical characteristics of the cable structure. The catalogs of manufacturers of power cables with cross-linked polyethylene insulation do not specify the long-term permissible load currents, which would take into account the cross-sectional area of the screen, the presence of aluminum polymer tape and armor made of aluminum wires. These components can have a significant impact on the permissible load due to the currents induced in them during two-way grounding, which leads to additional heating of the cable. The purpose of this study is to analyze the influence of the above-mentioned factors on the long-term permissible load currents. The paper presents formulas for calculating the long-term permissible load current, which take into account the design features of the cables under consideration. The calculations have shown that the permissible load can decrease by 6 % with an increase in the cross-sectional area of the screen from the nominal row by one step. The introduction of an aluminum polymer tape into the cable structure changes the permissible load by no more than 2 %. The presence of armor can lead to a decrease in the permissible load by up to 18 % and its increase by up to 13 %, depending on the section of the core and screen, the method and conditions of laying. The calculation results obtained differ from the catalogdata by up to 25%. While the obtained errorsindicatetheneed to formcoefficientsfor a moreaccuratedetermination of the long-term permissible cable currents.